VARIASI MORFOLOGI ULAR CANTIK MANIS, Tropidolaemus wagleri Wagler, 1830 (SERPENTES: VIPERIDAE) DI SUMATERA BARAT, INDONESIA - Kurniawan, Hadi; Tjong, Djong Hon; Novarino, Wilson (Metamorfosa: Journal of Biological Sciences; Vol 5 No 1 (2018), 2018)
Tropidolaemus wagleri commonly known as complex species who widely distributed at tropical areas in Southeast Asia. We predicted that widespread distribution may affect the morphological variation among different population geographycally. This study were conducted based on direct survey and sampling in the fieldwork. The study sites was divided into two categories based on Bukit Barisan range which streching from North to South Sumatra island consist of Padang, Padang Panjang in western part of Bukit Barisan, and Payakumbuh, Dharmasraya in eastern part of Bukit Barisan. In total 21 individual T.wagleri were analysed based on 20 mensural characters (morphometric) and 19 multistate characters (meristic). Male and female was analysed separately based on non parametric statistics Kruskall Wallis and Mann Whitney U Test. The relationship between population were analysed based on UPGMA tree and Principal Component Analysis (PCA) plot. The result showed the significant variation between female T. wagleri between western and eastern part of Buki Barisan range. In contrast, the variation has not detected among the population of T. wagleri male. The morphological character which showed the significant value are Head Length (HL) and Neck Scales Row (NSR). The west population of T. wagleri has more shorter Head Length (HL) and Snouth Length (SnL) than east population. Howefer, the west T. wagleri population has more number in Neck Scales Row (NSR) character than east population. The population of  female T. wagleri in Padang Panjang has more close relationship to Padang  than to female population T. wagleri in Dharmasraya based n UPGMA tree.